Economic Impacts of Wetland Amenities A Spatial Econometric Analysis of the Housing Market - René Van der Kruk (European Regional Science Association (ERSA), 2001)
Wetlands in the Netherlands are subject to pressures from various economic activities. Especially in the Randstad region there is a strong competition for land among residential industrial, natural and agricultural land use. In this part of the country, where land use is intensive, spatial spill-overs are quite relevant. The presence of externalities is the reason why land markets are heavily controlled in the Netherlands. In consultation with various interest groups Dutch national, regional and municipal governments have developed land use policies for some unique wetland areas. The economic impact of Dutch restrictive wetland use policies is manifest on housing markets. This effect is not limited to the construction of residential properties in the wetland surrounding areas. The regional housing price formation process is also affected by regulatory land use regimes. The aim of this paper is to focus on the economic impacts of Dutch restrictive wetland use policies. In particular a spatial econometric analysis of the housing market will be performed in order to determine the relationship between the presence of wetland areas and the prices of nearby houses. For this purpose, a database with selling prices and characteristics of houses from the Dutch brokers association (NVM) will be used. The neighbourhood effect mentioned above is estimated using spatial econometric techniques which are closely related to the hedonic pricing method, which determines the marginal value of various characteristics of a commodity. Also, a panel data analysis will be carried out in order to be able to reveal the in time dynamics of housing markets.
Keywords: 330